Utilização de resíduo de ETA no tratamento de efluente de lagoas de estabilização - Soares, Lorena Acelina (2013)
Water treatment plants (WTP) inevitably generates waste (WTPS) that must be disposed properly, however due to its characteristics can be reused in other processes such as polishing the effluent of stabilization ponds.This work was developed with the intention of use this waste in the wastewater treatment stabilization ponds, which have good characteristics of organic matter removal, but low efficiency in nutrient removal. Assays were performed in Jar Test equipment, wherethefactors: concentrations of the residue, gradient speed, pH and the time of mixing and sedimentation were varied. It was observed the influence of each factors in the removal of phosphorus, ammonia nitrogen organic, nitrate, COD, turbidity and true color. To obtain sufficient volume for analyze the residue formed after the addition of effluent from maturation pond with water treatment plant sludge (WTPS), sedimentation tests were performed on an acrylic column, using the natural pH of the effluent and a pH modified to 6,0. The residue formed in sedimentation test and the WTPS were characterized as structure and composition. The Jar Test assays showed that there was greater removal of total phosphorus (48,04%), COD (49,39%) and color (50,79%), and that the parameters and the factors had significantly influence in the removal.The waste from sedimentation tests and WTPS consist mainly of sand, silt and clay, and its structures are composed of the minerals kaolinite, halloysite and halite. It was concluded that the use of WTPS to polish the effluent from stabilization ponds proves to be a good alternative to the disposal of this waste, assisting in the removal of quality parameters of treated wastewater.